South Korea’s Potential Export Flow: A Panel Gravity Approach - Irshad, Muhammad Saqib; Xin, Qi; Shahriar, Saleh; Ali, Faizan (Asian Journal of Empirical Research, 2018)
This study examines the export flow of South Korea by utilizing pooled ordinary least square (OLS) along with time fixed effects by employing augmented gravity approach. It has also attempted to find out the potential market for South Korean exports. In this study, we analyze comprehensive panel dataset for time period 2001-16 (16 years) covering South Korea’s 189 importing nations. The result emerges robust to the requirement, time interlude and trade determinants. The empirical consequences are determined consistent through the gravity approach since the result discloses constructive coefficients for economic mass, bilateral exchange rate, trade agreements and trade openness in partner country and negative coefficients for distance and landlocked countries. The results also illustrate that the export pattern of South Korea hinges on the Heckscher-Ohlin (H-O) hypothesis, therefore be explicated by the dissimilarity in factor endowments for instance technology and advancement. We have found immense export potential with 94 countries including China, Japan, Hong Kong, Germany, France, Indian and the UK. Our analysis witnesses that strong policy implication and to diversification in the export leads South Korean exports at remarkable growth.